The Association between Monocyte Surface CD163 and Insulin Resistance in Patients with Type 2 Diabetes - Reina Kawarabayashi; Koka Motoyama; Miyuki Nakamura; Yuko Yamazaki; Tomoaki Morioka; Katsuhito Mori; Shinya Fukumoto; Yasuo Imanishi; Atsushi Shioi; Tetsuo Shoji; Masanori Emoto; Masaaki Inaba (Journal of Diabetes Research)
Aim. To investigate the association between monocyte CD163 and insulin resistance in patients with type 2 diabetes. Methods. One hundred sixty-six patients with type 2 diabetes without inflammatory or chronic kidney disease were recruited. The monocyte CD163 levels were measured by flow cytometry and soluble CD163 (sCD163) by ELISA. Insulin resistance was evaluated by the index of the homeostasis model assessment (HOMA-R). Results. The median sCD163 and monocyte CD163 expression levels were 582.9 (472.4–720.0) ng/ml and 6061 (4486–7876) mean fluorescent intensity (MFI), respectively. In a simple regression analysis, monocyte CD163 was inversely correlated with log [HOMA-R] (r=–0.257, p=0.010), and sCD163 was positively correlated with log [HOMA-R] (r=0.198, p=0.042). In multiple regression analyses, monocyte CD163 was an independent contributor to log [HOMA-R] (β=–0.220, p=0.020) even after adjustment of various clinical factors for HOMA-R (R2=0.281, p=0.001), whereas sCD163 was not. Conclusions. Monocyte surface CD163 expression levels were more significantly associated with insulin resistance than sCD163 in patients with type 2 diabetes, suggesting a novel pathophysiological role of CD163.